Ayurvedic Therapeutic Management of a Chronic Liver Disease With Progressed Chronic Liver Failure: A Clinical Case Study - Manish, Acharya; Richa; Thakur, Preeti; Chandrasekharan, Prabha (International Research Journal of Ayurveda & Yoga, 2026)
Chronic Liver Failure (CLF), evolving from long-standing Chronic Liver Disease (CLD), is a progressive condition marked by impaired liver function and systemic complications. In Ayurveda, it is understood as a manifestation of aggravated Pitta Dosha, particularly Ranjaka Pitta, resulting in Ama accumulation, Rakta Dushti, and Srotorodha, leading to conditions akin to Kamala, Yakritodar, or Kumbhak Kamala. This case report presents a 37-year-old male with CLF and associated features such as Mukha – Pada Shotha (facial and pedal oedema), Peeta Netra (jaundiced sclera), Daurbalya (weakness), and Vibandh (constipation). A 14-day integrative Ayurvedic protocol including Panchakarma therapies, classical formulations, and dietary modifications was administered. Marked clinical and biochemical improvements were observed post-treatment, including reduced bilirubin levels, improved haemoglobin, and relief in oedema and fatigue. The outcome highlights the efficacy of individualized Ayurvedic management in restoring Agni, correcting Pitta Dushti, and enhancing overall quality of life in CLF patients.